CОВЕТСКАЯ ШКОЛА В ЗАПАДНЫХ ОБЛАСТЯХ БССР 1939 – 1941 гг.: ХАРАКТЕРИСТИКА ПРОГРАММ, ФУНКЦИИ ШКОЛЫ, ФРОНТ ДЕЯТЕЛЬНОСТИ (Zaporizhzhia Historical Review, 2021)
At the end of 1939/40 academic year school in the western regions of Belarus can be already called soviet: the content of schools’ schedules, out-of-class and extra-curricular activities approximately corresponded to the aims which were set to school, namely, to arrangeа process of bringing up “sovietman”. 1940/41 academic year was going under the influence of unification and the soviet Enlightenment of that time. The unification was characterized by predominance of communist ideology and the sciences, antireligious trends and intensification of attention towards military – physical training.